A surface‐enhanced Raman sensor for trace identification and analysis of high‐priority drugs of abuse with portable and handheld Raman devices. (10th July 2022) - Zhang, Tingting; Pei, Junchang; Li, Xuefeng; Li, Haowen; Inscore, Frank
Abstract: Surface‐enhanced Raman spectroscopy (SERS) is a rapidly emerging technology that offers a fast, extremely sensitive, and quantitative approach to trace chemical detection. Such a technique incorporated into a portable device is attractive to law enforcement and emergency room personnel for rapid accurate on‐site screening of illicit and abused drugs. Toward this, we are developing an analyzer in a hand‐held unit, based on SERS that is integrated with a capillary sensor embedded with activated gold nanoparticles in a porous glass matrix. In this preliminary study, we have used this gold sol–gel capillary to measure aqueous solutions of 14 high‐priority drugs to define sensitivity (lowest measured concentration [LMC] and estimated limit of detection [LOD]), determine concentration dependence and quantification capabilities by constructing calibration curves, examine effects of pH at 3, 7, and 11 on SERS measurements, and perform multicomponent analysis of fentanyl laced drug mixtures and spectral identification on our portable and handheld units. Of particular significance, fentanyl was detected with an LMC of 1 ng/ml and estimated LOD at 0.11 ng/ml, while other representative drugs such as cocaine and phenylcyclidine produced LMCs and LODs at 5.0 and 0.77 ng/ml, and 10.0 and 0.62 ng/ml, respectively. These sub‐nanogram per milliliter detection limits are comparable or lower than previously reported and confirm that this gold sol–gel has the potential to meet the sensitivity requirements for saliva analysis. Most importantly, these sensors can be manufactured easily and cheaply and when integrated with our portable Raman units produce high‐quality spectra and accurate identification within 1.2 s. Abstract : We have used surface‐enhanced Raman spectroscopy (SERS) to quantitatively detect 14 high‐priority illicit and abused drugs with a sensor embedded with activated gold nanoparticles in a porous glass matrix. This gold sol–gel provides an alternative to typical silver and gold colloids. We report excellent sensitivity with sub‐nanogram per milliliter detection on representative drugs such as cocaine (stimulant), fentanyl (opioid), and phenylcyclidine (hallucinogen). This gold sol–gel capillary is shown to be very stable even under extreme acidic and basic pH conditions.